2017
DOI: 10.3389/fnhum.2017.00233
|View full text |Cite
|
Sign up to set email alerts
|

Fast Brain Plasticity during Word Learning in Musically-Trained Children

Abstract: Children learn new words every day and this ability requires auditory perception, phoneme discrimination, attention, associative learning and semantic memory. Based on previous results showing that some of these functions are enhanced by music training, we investigated learning of novel words through picture-word associations in musically-trained and control children (8–12 year-old) to determine whether music training would positively influence word learning. Results showed that musically-trained children outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 93 publications
10
48
1
1
Order By: Relevance
“…In addition, on the basis of previous evidence showing a main contribution of the middle-posterior part of the middle temporal gyrus to lexical-semantic access at the world level, 44,79 connectivity in the ventral stream was evaluated between the IP lobe and Brodmann's area 21 (i.e., control region). In line with previous studies, 26,27 musicians were characterized by a behavioral advantage in word learning that originated from a lower false alarm rate. This behavioral advantage was paralleled by a left-hemispheric functional asymmetry in the dorsal stream in the theta frequency range, whereas nonmusicians showed an almost symmetric recruitment of the same circuit.…”
Section: Neural Network and Word Learningsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, on the basis of previous evidence showing a main contribution of the middle-posterior part of the middle temporal gyrus to lexical-semantic access at the world level, 44,79 connectivity in the ventral stream was evaluated between the IP lobe and Brodmann's area 21 (i.e., control region). In line with previous studies, 26,27 musicians were characterized by a behavioral advantage in word learning that originated from a lower false alarm rate. This behavioral advantage was paralleled by a left-hemispheric functional asymmetry in the dorsal stream in the theta frequency range, whereas nonmusicians showed an almost symmetric recruitment of the same circuit.…”
Section: Neural Network and Word Learningsupporting
confidence: 89%
“…Currently, there is a growing body of interest in better understanding whether music training may facilitate different aspects of speech processing, including spectrotemporal analyses, [25][26][27][28][29] hearing speech in noise, [30][31][32] speech segmentation, 33,34 phonetic discrimination learning, 35 and word learning. 26,27 For example, by using a longitudinal approach in children undergoing music training or painting for a period of 9 months, Moreno and colleagues 36 were able to demonstrate a causal relationship between music training and enhanced reading and pitch discrimination abilities in speech. Furthermore, Francois and coworkers 33 performed a longitudinal study over 2 years using a test-training-retest procedure to examine the influence of music training on speech segmentation in 8-year-old children.…”
Section: Relationships Between Music Training Spectrotemporal Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more recent work has, in a similar vein, asserted the earlier and more frontal N400 to index online speech segmentation, although in that work the frontal negativity was linked to novel word-form to conceptual knowledge mapping in parallel (e.g. Cunillera et al, 2009; Dittinger et al, 2017; François et al, 2017). So while the frontal N400 (or N325) is not yet fully understood, and has led to slightly different views as to what it precisely represents, there seems to be some common ground with phonological/metrical expectancy influencing semantic processing.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent results also revealed that both short-and long-term music training have a positive influence on diverse cognitive functions, including auditory- (Strait, Slater, O'Connell, & Kraus, 2015) and visual attention (Wang, Ossher, & Reuter-Lorenz, 2015), short-term-, working-and verbal memory (George & Coch, 2011;Schulze & Koelsch, 2012), and on general executive functions (Zuk et al, 2014). Based on such a multifaceted influence of music training on speech processing and cognition, Dittinger and collaborators recently examined the influence of music training on novel word learning in adults (Dittinger et al, 2016) and in 8-12-yearold children (Dittinger, Chobert, Ziegler, & Besson, 2017). Thereby, the authors focused on the development of the N400 component and on the N400 effect (unexpected minus expected words) as an index of novel word learning (frontal N400 or FN400 in a learning phase) and retrieval from episodic and semantic memory (in matching and semantic tasks).…”
mentioning
confidence: 99%